Sirtuins: Possible Clinical Implications in Cardio and Cerebrovascular Diseases - Conti, Valeria; Forte, Maurizio; Corbi, Graziamaria; Russomanno, Giusy; Formisano, Luigi; Landolfi, Alessandro; Izzo, Viviana; Filippelli, Amelia; Vecchione, Carmine; Carrizzo, Albino (Current Drug Targets, 2017)
Mammalian sirtuins (SIRT1-7) are NAD+-dependent deacetylases, which play an important role in aging and in a wide range of cellular functions. SIRT1, the best-characterized member of the family, acts as a sensor of the redox state and triggers in the cell the appropriate defense response. A large body of evidence has showed that SIRT1 induces both cellular and systemic protective effects in the cardiovascular system by preventing stress-induced apoptosis and senescence, and mitigating endothelial dysfunction. Hence, SIRT1 is now foreseen as a potential therapeutic target for a growing number of cardiovascular diseases. Recently, it has been suggested that SIRT1 activation could also be considered as a neuroprotective strategy. Indeed, SIRT1 protects against ischemia/reperfusion injury both in vitro and in vivo and avoids severe ischemic damage by preserving cerebral blood flow. In the last years it was suggested that others sirtuins, in particular SIRT3 and SIRT6, could exert beneficial effects in vascular syndromes. The aim of this review was to describe and discuss recent experimental evidence on the effects of SIRT1 and other sirtuins on the pathophysiology of cardio- and cerebrovascular diseases, underlying a potential therapeutic effect of these enzymes in the treatment and/or prevention of such conditions.
Keywords: drugs